الهدر الدلالي للعلامة المكانية في الخطاب الدرامي التلفزيوني - مولى سيد علي (Journal of College of Education, 2021)
The current research deals with the importance of place as a sign within the fabric of dramatic television discourse and how it is used to charge the dramatic discourse with the greatest amount of expression energy, which in turn conveys a set of social, psychological and economic connotations to the characters that drive the action Within the construction of the drama series on the basis that the place is the container for the characters, which in turn are the ones that move the action and lead the building to escalation, conflict and resolution later, at a time when we find that there is a weakness in the operation of the place and the activation of the expressive scientific levels, So that place becomes an inanimate entity that does not exceed the threshold of purely employable employment for the purpose of housing, accommodation, work or study, The waste of the semiotic value of the place goes to a wider waste in the overall semantic speech system until the whole system of expression works to the minimum and there is no relationship between the signs that raises the The expressive value and thus the aesthetic value of that discourse.